Augmented Reality Art From an Emerging Technology to a Novel Creative Medium - Geroimenko, Vladimir (Springer Series on Cultural Computing,, 2014)
Written by a team of world-renowned artists, researchers and practitioners - all pioneers in using augmented reality based creative works and installations as a new form of art - this is the first book to explore the exciting new field of augmented reality art and its enabling technologies.    As well as investigating augmented reality as a novel artistic medium the book covers cultural, social, spatial and cognitive facets of augmented reality art.  Intended as a starting point for exploring this new fascinating area of research and creative practice it will be essential reading not only for artists, researchers and technology developers, but also for students (graduates and undergraduates) and all those interested in emerging augmented reality technology and its current and future applications in art.